Incidental diagnosis of presacral ganglioneuroma in a patient with hematuria - Asra Nayab, MBBS; Muhammad Hammad Malik, MBBS; Ajay A. Madhavan, MD; James Glockner, MD; Douglas A. Collins, MD; Doris E. Wenger, MD (Radiology Case Reports, 2023)
Ganglioneuromas are benign neuroblastic tumors seen most in pediatric population. The most common locations are mediastinal, retroperitoneal and adrenal regions. Ganglioneuromas rarely occur in presacral space. We present one such case of an incidentally diagnosed presacral ganglioneuroma in an asymptomatic 71-year-old male who initially presented with hematuria.